Pathways to Drug and Sexual Risk Behaviors among Detained Adolescents - Voisin, Dexter R. (2008)
PURPOSE: Among a sample of detained youth, to investigate pathways that link witnessing community violence, in the 12 months prior to being detained, to drug and sexual risk behaviors, in the two months preceding detainment. METHODS: Using A-CASI technology, data was collected from 559 detained adolescents on demographics, family factors, peer influences, religiosity, witnessing community violence, and drug and sexual risk behaviors. RESULTS: Controlling for demographics and family variables, findings indicated positive associations between witnessing community violence and drug and sexual risk behaviors. Witnessing community violence was directly linked to sexual risk behaviors, and indirectly associated with these risk behaviors, through gang membership and perceived risky peer norms. Additionally, witnessing community violence was indirectly linked to substance use through gang membership and perceived risky peer norms. CONCLUSIONS: Interventions targeting change in peer affiliations and perceived norms may be an effective strategy for reducing risky drug and sexual behaviors among detained youth.